Attention please! - Olivier Gossner; Jakub Steiner; Colin Stewart (University of Zurich, Department of Economics, 2018)
We study the impact of manipulating the attention of a decision-maker who learns sequentially about a number of items before making a choice. Under natural assumptions on the decision-maker's strategy, forcing attention toward one item increases its likelihood of being chosen.
Keywords: D8; D91; 330; sequential sampling; marketing; persuasion; attention allocation